2007
DOI: 10.1053/j.gastro.2006.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Expression of p11 and SERT in Mucosal Biopsy Specimens of Patients With Irritable Bowel Syndrome

Abstract: Background/Aim-The pathophysiology of irritable bowel syndrome (IBS) remains enigmatic; abnormalities in serotonin metabolism have been implicated. Two proteins that influence the function of serotonin and serotonergic receptors are serotonin transporter protein (SERT or soluble carrier protein SLC6A4) and p11 (S-100A10, or calpactin I light chain). Both proteins are reported to be associated with depression-like states, a frequent co-morbid condition in IBS. We explored the hypothesis that expression of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 28 publications
8
69
3
Order By: Relevance
“…Although Bellini et al (3) suggested that platelet SERT should reflect colonic SERT in IBS and observed a significant relationship with IBS-D, the assumption has not been validated or rigorously tested. Coates et al (16) suggested that there was an association between IBS-C or IBS-D and reduced SERT mRNA mucosal expression; however, we were unable to replicate the association between IBS symptom phenotype and SERT mRNA in sigmoid colon mucosa (7).…”
Section: Discussioncontrasting
confidence: 68%
“…Although Bellini et al (3) suggested that platelet SERT should reflect colonic SERT in IBS and observed a significant relationship with IBS-D, the assumption has not been validated or rigorously tested. Coates et al (16) suggested that there was an association between IBS-C or IBS-D and reduced SERT mRNA mucosal expression; however, we were unable to replicate the association between IBS symptom phenotype and SERT mRNA in sigmoid colon mucosa (7).…”
Section: Discussioncontrasting
confidence: 68%
“…It is reported that in patients with IBS, the level of serotonin transporter protein mRNA and serotonin transporter protein decreased significantly in the intestinal epithelial cell 54) . Interestingly, these findings have not been proved in a current study 55) . But, some studies showed the description of a link between a protein critical to serotonin receptor functions and IBS 55) .…”
Section: Genetic Effectscontrasting
confidence: 91%
“…paratuberculosis infection and disease in animals may reflect a specific mycobacterial neuropathogenicity. Microscopic inflammation affecting the enteric nervous system, together with abnormalities affecting its function and regulation, is well described in cases of IBS (2,4,11,19,25,51,69). Those studies have led to advances in our understanding of how these features integrate into the underlying pathophysiological mechanisms of the syndrome (3,32,48).…”
Section: Discussionmentioning
confidence: 99%